2023
DOI: 10.11591/ijai.v12.i3.pp1323-1329
|View full text |Cite
|
Sign up to set email alerts
|

Classification of customer churn prediction model for telecommunication industry using analysis of variance

Abstract: Customer predictive analytics has shown great potential for effective churn models. Thriving in today's telecommunications industry, discerning between consumers who are likely to migrate to a competitor is enormous. Having reliable predictive client behavior in the future is required. Machine learning algorithms are essential to predict customer turnovers, and researchers have proposed various techniques. Churn prediction is a problem due to the unequal dispersal of classes. Most traditional machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Authors confirmed that they achieved an accuracy rate of 80% in telecom customer churn prediction. Babatunde et al [20] used a hybrid approach which combined analysis of variance (ANOVA) with SVM to predict customer's churn. The authors confirmed that they successfully predicted future churns with an accuracy rate that reached 95%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors confirmed that they achieved an accuracy rate of 80% in telecom customer churn prediction. Babatunde et al [20] used a hybrid approach which combined analysis of variance (ANOVA) with SVM to predict customer's churn. The authors confirmed that they successfully predicted future churns with an accuracy rate that reached 95%.…”
Section: Literature Reviewmentioning
confidence: 99%